Islamic law of contract - Razali, Siti Salwani (Cengage Learning Asia, 2010)
This book revolves around the issues on the formation of contract under Common Law and also Islamic Law. All the elements of contract are discussed in detail in this book. The author has made a comparison on the issues between Common Law and Islamic Law to give the reader a clear understanding of the elements of contract and all other issues in contract law; for example the issue of gharar and the notion of khiyar under Islamic Law and the doctrine of mistake, both under Common Law and Islamic Law. This book is suitable for all readers, be they undergraduate and graduate students or professionals who wish to know more about contract law especially from the Islamic perspective.